Understanding the Complex Structure of a Plant-Floral Visitor Network from Different Perspectives in Coastal Veracruz, Mexico - Haydée Hernández-Yáñez (Universidade Estadual de Feira de Santana, 2013)
Our premise was to understand the basic structure of the flower-flower visitor community at La Mancha in Veracruz, Mexico. We used network analyses to study the structure of this community. In particular, to analyze, (1) if flower color and shape (“as a limited portion of the traditional floral syndromes definition”) were linked to the arrival of certain floral visitors, (2) if visits to flowers were generalist, specific and/or modular; and (3) which plant species, if any, in the core of the network could affect the stability of floral visitors. In order to analyze the organization of the plant-floral visitor community, we prepared network graphics using Pajek, nestedness (as NODF) with Aninhado, and modularity with the SA algorithm. The network obtained was nested suggesting that generalist species (with the most associations) were interacting with specialists (with fewer associations). Furthermore, floral visitors (Hymenoptera, Diptera, Lepidoptera and Trochiilidae) did not exhibit a particular preference for a specific flower color or shape, each pollinator group visited most flowers/colors/shapes considered. The same was similar for all 14 resulting modules. As in other studies, we suggest that pollination leans to generalization rather than to specialization. We suggest that maybe seasonality/food resource could be the factors to analyze as the next step in floral visits which may be the answer to modularity in this seasonal ecosystem.